2017
DOI: 10.17951/i.2016.41.2.47
|View full text |Cite
|
Sign up to set email alerts
|

Opieka okołoporodowa w Polsce po transformacji ustrojowej – między medykalizacją a demedykalizacją?

Abstract: <p><span>Od początku lat 90. XX w. nastąpiło wiele zmian w zakresie świadczenia opieki nad kobietą w okresie okołoporodowym oraz nad noworodkiem. Zmiany te są przykładem występującej równolegle do procesu medykalizacji tendencji do demedykalizacji. Celem artykułu jest przedstawienie zmian w zakresie opieki okołoporodowej po transformacji ustrojowej oraz analiza tych przeobrażeń z perspektywy teorii medykalizacji. W pracy staram się scharakteryzować opiekę okołoporodową w Polsce na początku XXI w. w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…A high rate of medicalization in obstetrics, e.g. an increased percentage of cesarean sections, poses a threat to the professional position of midwives because medical care plays a greater role in such cases 21 . Chakrabory et al 22 reported an alarming shortage of midwives whose services were crucial to meeting the health needs of women and children.…”
Section: Discussionmentioning
confidence: 99%
“…A high rate of medicalization in obstetrics, e.g. an increased percentage of cesarean sections, poses a threat to the professional position of midwives because medical care plays a greater role in such cases 21 . Chakrabory et al 22 reported an alarming shortage of midwives whose services were crucial to meeting the health needs of women and children.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the demand for epidurals is high. Based on information collected from over 8000 women who gave birth in 2017 and 2018, 23.7% of women in Poland received an epidural [ 67 ] and more may have wanted it—13% of women declared that they were not given an epidural even though they requested it.…”
Section: Discussionmentioning
confidence: 99%
“…In Poland, c-section rates rose rapidly in the last decade from below 20% in 2007 to 39.3% in 2017 [ 28 ]. This is one of the highest c-section rates among OECD countries, despite many improvements over this time to Polish hospitals and very good standards of perinatal care [ 67 ]. Our study is among the first population-based studies of the mode of birth in Poland and shows that lack of continuous personal support and the use of epidurals both increase the odds of a c-section over vaginal birth.…”
Section: Discussionmentioning
confidence: 99%
“…Since the political transformations in 1989, many changes have taken place in Poland's perinatal care system (Doroszewska, 2016).…”
Section: Polish Perinatal Care Contextmentioning
confidence: 99%